2007
DOI: 10.1093/sjaf/31.2.60
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Compliance of Forestry Best Management Practices in West Virginia

Abstract: The compliance of forestry best management practices (BMP) was assessed based on 116 randomly selected sites harvested between November 2003 and March 2004 in West Virginia. Landowners were contacted to gain permission for site visits according to the random list. The landowners also were interviewed to identify their knowledge and satisfaction about the harvest and BMP. Four checklists were used to assess 29 BMPs on haul roads, skid trails, landings, and in streamside management zones (SMZ). A general increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this study, a sensitivity analysis is conducted for biomass/coal weight ratios of 8:92, 15:85, and 20:80 (dry) to estimate the effect of feedstock composition on the plant performance, especially the product yield and plant efficiency. A relatively low biomass content is considered in this study mainly considering sustainability of the plant . For the alternative cases, the total amount of dry feed and other design parameters are fixed to be the same as the base case.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a sensitivity analysis is conducted for biomass/coal weight ratios of 8:92, 15:85, and 20:80 (dry) to estimate the effect of feedstock composition on the plant performance, especially the product yield and plant efficiency. A relatively low biomass content is considered in this study mainly considering sustainability of the plant . For the alternative cases, the total amount of dry feed and other design parameters are fixed to be the same as the base case.…”
Section: Resultsmentioning
confidence: 99%
“…However, their work also showed a substantial increase in water quality and control of silvicultural non-point source pollution as a result of the transition from a voluntary model with a compliance rate of 42 percent to a more stringent inspection based model with a compliance rate of 92 percent, and to a lesser extent with a transition to a regulatory model with an assumed compliance rate of 95 percent. Wang et al (2007) Regulatory enforcement of forestry BMPs has also been shown to be very effective in achieving the goals of stream sedimentation mitigation, as well as improving overall forest health. The combination of state agency logger education and training, along with the ever-improving scientific understanding and implementation of forestry BMP regulations has led to significant gains in non-point source stream sedimentation mitigation, improved forest health, and the protection of landowner property.…”
Section: Evaluated Timber Harvesting Operations In Northern Westmentioning
confidence: 99%
“…Not taking into account these new samples, overall compliance remained generally static with past years. West Virginia's BMP compliance rates generally equivalent with other northeastern states Wang et al (2007). studied the compliance rates in West Virginia given the passing of time since the last compliance study.…”
mentioning
confidence: 99%